TPACK Competence and Technology Use Among in-Service EFL Teachers - Sukarni, Semi; Chasanah, Zulia; Maskuri, Edi Sunjayanto; Laksono, Puji; Anua Jah, Nurain Jantan (JOLLT Journal of Languages and Language Teaching, 2025)
In the context of teacher professionalism, the ability to effectively integrate technology into teaching practices is now part of the basic competencies that must be possessed. One of the conceptual frameworks that are widely used to measure and assess this competency is Technological Pedagogical and Content Knowledge (TPACK). Therefore, this study aims to (1) describe how in-service English teachers integrate technology into their EFL teaching, and (2) explain the perceptions of these teachers regarding their TPACK competency. The research is a mixed-method study that combines quantitative and qualitative data collection using observation and questionnaires. Thirty teachers consisting 11 male and 19 female involved in this study.Â The quantitative data were analyzed using descriptive analyses, while the qualitative data were analyzed using thematic analysis by presenting themes and codes. Â The finding of the study shows that in-service English teachers have "good" competence of TPACK as shown in the mean of the questionnaire result is 3.94 which belongs to the good category. Among 7 TPACK categories, TPK is the highest with the mean 4.14, on the other hand, PCK is the lowest with a mean 2.94. There are 16 types of ICT integrated in their lesson. PPT, blog, Pinterest, and YouTube are mostly used their English lesson with 100% on the other hand, Link Tree and Elsa Speak is the lowest used. Overall, these findings underscore the importance of further training that focuses not only on the use of technology, but also on how it can be effectively linked to content and pedagogical approaches in the context of English language learning.